Population and individual-level predicting of blood pressure - M. M. Batyushin; V. P. Terentyev (Российский кардиологический журнал)
During regional population family survey, 1298 of Rostov-on-Don City and Region citizens were examined. Mean age was 42, 61 ± 0, 58 years. There were 527 men and 771 women; total number of families surveyed was 270. Correlation and regression analyses, as well as special population-level genetic analysis methods, were used. Prognostic models were developed in two- and multivariate regression analysis, with regression equation construction. Multiple regression equations, predicting systolic and diastolic blood pressure levels, could be used in medico-genetic counseling and population screening programs, to identify arterial hypertension high-risk groups.